Bispecific human IL2‐CCR4 immunotoxin targets human cutaneous T‐cell lymphoma. Issue 5 (13th March 2020) - Wang, Haoyu; Wang, Zhaohui; Zhang, Huiping; Qi, Zeng; Johnson, Ariel C.; Mathes, David; Pomfret, Elizabeth A.; Rubin, Erin; Huang, Christene A.; Wang, Zhirui
Abstract : The majority of clinically diagnosed cutaneous T‐cell lymphomas (CTCL) highly express the cell‐surface markers CC chemokine receptor 4 (CCR4) and/or CD25. Recently, we have developed diphtheria toxin‐based recombinant Ontak®‐like human IL2 fusion toxin (IL2 fusion toxin) and anti‐human CCR4 immunotoxin (CCR4 IT). In this study, we first compared the efficacy of the CCR4 IT vs IL2 fusion toxin for targeting human CD25 + CCR4 + CTCL. We demonstrated that CCR4 IT was more effective than IL2 fusion toxin. We further constructed an IL2‐CCR4 bispecific IT. The bispecific IT was significantly more effective than either IL2 fusion toxin or CCR4 IT alone. The bispecific IT is a promising novel targeted therapeutic drug candidate for the treatment of refractory and recurrent human CD25 + and/or CCR4 + CTCL. Abstract : We have developed an IL2‐CC chemokine receptor 4 (CCR4) bispecific immunotoxin (IT). The bispecific IT was significantly more effective than either IL2 fusion toxin or CCR4 IT alone. The bispecific IT is a promising novel targeted therapeutic drug candidate for the treatment of refractory and recurrent human CD25 + and/or CCR4 + cutaneous T‐cell lymphoma.